Risk Factors of Maternal Mortality - Khansa Iqbal, Fehmida Shaheen, Attiya Begum, (Journal of Rawalpindi Medical College, 2014)
Background: To analyze maternal deaths, the risk factors involved and the contribution of each risk factor towards maternal mortality. Methods: In this descriptive study a complete evaluation of all maternal deaths was performed. All maternal mortalities were presented and evaluated in monthly hospital mortality meetings. Information was collected about women booking status, age, parity, socioeconomic status, distance from place of referral, and reasons for delayed referral. Women who received antenatal care at least three times in the hospital were labeled as booked and rest of patients as non booked. The causes and factors leading to maternal deaths were recorded. Results:During this period total numbers of deaths certified were 51. Out of these 8 patients were brought dead to hospital while 43 died in hospital. Direct causes were found in 41 maternal deaths (80.3%). Hemorrhage being the leading cause (31.3%) followed by hypertensive disorders of pregnancy (eclampsia) and sepsis. Majority (90.0%) of maternal deaths were amongst non booked patients. Fifty three maternal deaths occurred in less than 24 hours of hospital admission. Different socio economic and cultural factors along with medical disorder played a vital role in women who were received dead. Conclusion: Majority of maternal deaths in tertiary care hospitals occur in non booked women referred from elsewhere in moribund condition.